Endophyte diversity and its correlation with naphthoquinone metabolites in cultivated Arnebia euchroma across different growth years - Jinrong Zhao; Jingjing Chen; Xuejia Zhang; Yanjiao Wang; Haiyan Xu (PLoS ONE, 2026)
Previous studies on Arnebia euchroma (Royle) Johnst. have focused on its physicochemical and pharmacological properties, and studies on the differences in metabolites in A. euchroma have also highlighted the effects of external environmental factors. In this study, we compared the differences in the diversity of endophytes in the root tissue of A. euchroma grown for 1–4 years in Hejing County using high-throughput sequencing and analyzed their relationship with eight secondary metabolites, including alkannin, β , β -dimethylacrylshikonin, deoxyshikonin, acetylshikonin, β -acetoxyisovalerylshikonin, β -hydroxyisovalerylshikonin, isobutyrylshikonin, and isovalerylshikonin. The results indicate that a total of 1161 amplicon sequence variants (ASVs) of endophytic fungi from cultivated A. euchroma were classified into 12 phyla, 32 classes, 76 orders, 153 families, 259 genera, and 367 species. Additionally, 673 amplicon sequence variants (ASVs) of endophytic bacteria were classified into 18 phyla, 37 classes, 89 orders, 139 families, 226 genera, and 267 species. The α-diversity of endophytic fungi and bacteria in cultivated A. euchroma peaked in four-year-old (X-4Z) and two-year-old (X-2Z) respectively. Spearman’s correlation analysis showed that β -hydroxyisovalerylshikonin, acetylshikonin, isobutyrylshikonin, β,β -dimethylacrylshikonin, and isovalerylshikonin were correlated with endophytic fungal diversity and abundance ( P ≤ 0.05 ). FUNGuild and PICRUSt2 predictive analyses showed that the dominant trophic modes of endophytic fungi in all samples were saprotrophic and pathotrophic, with the highest relative abundance in X-4Z, while the main trophic mode of endophytic bacteria was metabolic. Our results help to elucidate the importance of plant-microbe interactions and provide key information on the role of endophytes in promoting the cultivation of A. euchroma and the accumulation of its important secondary metabolites. They also provide a reference for further research on the effects of differences in the community composition of endophytes on the accumulation of medicinal compounds in A. euchroma and for the development of resources for its cultivation.